2018
DOI: 10.1039/c8ta02622j
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal speciation as a degradation mechanism with the formation of a solid-electrolyte interphase (SEI) in Ni-rich transition metal oxide cathodes

Abstract: An ever-growing demand for high-energy density and high-power Li-ion batteries has driven active research for electrode materials with superior capacity. Recent years have seen the development of Ni-rich transition metal oxide cathode materials due to their high reversible capacity and lower cost. To achieve full capacity from the charge compensation process, a high voltage (>4.4 V) charging is required. However, the battery operation at higher voltages eventually results in dramatic capacity fading and voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 74 publications
1
29
0
1
Order By: Relevance
“…As a consequence, the LiPF 6 salt may undergo the following dissociation reaction: LiPF 6 ⇌ LiF + PF 5 , followed by the hydrolysis of PF 5 : PF 5 + H 2 O → POF 3 + 2HF, according to Aurbach and Heider's theory . Additionally, the electrolyte decomposition will be accelerated as the Ni‐rich cathodes operate at high cutoff voltages and operation temperatures . Accordingly, the detrimental side reactions are triggered, leading to the serious dissolution of TM ions, which follows a trend of Mn > Co > Ni, as reported by Sun and co‐workers .…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 77%
“…As a consequence, the LiPF 6 salt may undergo the following dissociation reaction: LiPF 6 ⇌ LiF + PF 5 , followed by the hydrolysis of PF 5 : PF 5 + H 2 O → POF 3 + 2HF, according to Aurbach and Heider's theory . Additionally, the electrolyte decomposition will be accelerated as the Ni‐rich cathodes operate at high cutoff voltages and operation temperatures . Accordingly, the detrimental side reactions are triggered, leading to the serious dissolution of TM ions, which follows a trend of Mn > Co > Ni, as reported by Sun and co‐workers .…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 77%
“…have reported that transition metal speciation into various oxidation and spin states during charged to higher voltage, and the deposition of the modified TM as SEI species cause the dramatic capacity fading and voltage decay of Ni‐rich cathodes. [ 25 ] The correlation between TM dissolution and the cut‐off voltage could be i) increasingly exposed surfaces due to particle cracking by high‐voltage charging; ii) the widening of the TMO band due to the oxygen loss by high‐voltage charging and iii) the phase transition induced by high‐voltage charging.…”
Section: The Degradation Pathway Of Ni‐rich Layered Cathodes Under Hamentioning
confidence: 99%
“…It is observed that a reduction peak appeared at~0.71 V in the first discharge as a possible result of the typical redox features of transition metal oxides system. 25 Accordingly, two oxidation peaks appeared at~1.61 and 1.84 V during the first charge and can be attributed to the oxidation process. 26 However, the reduction peak during the second cycle is shifted to higher voltage of about 0.85 V, corresponding to the activation of active materials.…”
Section: Electrochemical Characteristics Of Znco 2 O 4 /C Microhydrmentioning
confidence: 96%